Δ9-tetrahydrocannabivarin impairs epithelial calcium transport through inhibition of TRPV5 and TRPV6. (October 2018) - Janssens, Annelies; Silvestri, Cristoforo; Martella, Andrea; Vanoevelen, Jo M.; Di Marzo, Vincenzo; Voets, Thomas
Graphical abstract: Abstract: Compounds extracted from the cannabis plant, including the psychoactive Δ 9 -tetrahydrocannabinol (THC) and related phytocannabinoids, evoke multiple diverse biological actions as ligands of the G protein-coupled cannabinoid receptors CB1 and CB2. In addition, there is increasing evidence that phytocannabinoids also have non-CB targets, including several ion channels of the transient receptor potential superfamily. We investigated the effects of six non-THC phytocannabinoids on the epithelial calcium channels TRPV5 and TRPV6, and found that one of them, Δ 9 -tetrahydrocannabivarin (THCV), exerted a strong and concentration-dependent inhibitory effect on mammalian TRPV5 and TRPV6 and on the single zebrafish orthologue drTRPV5/6. Moreover, THCV attenuated the drTRPV5/6-dependent ossification in zebrafish embryos in vivo . Oppositely, 11-hydroxy-THCV (THCV−OH), a product of THCV metabolism in mammals, stimulated drTRPV5/6-mediated Ca 2+ uptake and ossification. These results identify the epithelial calcium channels TRPV5 and TRPV6 as novel targets of phytocannabinoids, and suggest that THCV-containing products may modulate TRPV5- and TRPV6-dependent epithelial calcium transport.